Energy-environment-economic investigations on evacuated active multiple stage series flow solar distillation unit for potable water production. (1st November 2017) - Reddy, K.S.; Sharon, H.
Highlights: Energy, environment and economic analyses of active solar distillation unit. Parametric study on active multiple stage series flow solar distillation unit. Distillate yield enhancement by evacuation and evaporative cooling. Harmful emission mitigation potential assessment based on year round analysis. Economic feasibility assessment of proposed solar distillation unit. Abstract: Multi stage solar distillation units are well known for their higher distillate productivity and are capable of fulfilling the potable water requirements of families in remote, rural, and coastal regions. In this article, active multiple stage series flow solar distillation unit has been proposed for desalting saline water and its performance, environmental benefits and economic feasibility were assessed by carrying out 3E (Energy-Environment-Economic) analyses using the developed mathematical model. Better performance was observed for the distillation unit with five distillation stages, two solar collectors connected in parallel configuration and saline water mass flow rate of 135.0 kg/d and 75.0 kg/d, during summer and winter seasons. Low-pressure operation in combination with evaporative cooling of condenser of last stage has enhanced the annual average daily distillate productivity from 12.60 kg/d to 48.80 kg/d. Distillate production was found to drop from 48.80 kg/d to 38.90 kg/d with the increase in salt concentration of saline water from 0 wt% to 10 wt%. Energy payback time of the unit desalting saline water with 5 wt% salt concentration was within 1.0 yr and the unit can mitigate nearly 221.80 tons of CO2 emission, 1594.73 kg of SO2 emission and 651.37 kg of NO emission from Indian coal based power plants during its 20 yrs lifespan under 250 clear day operation. Increased salt concentration in saline water reduces the emission mitigation potential and increases the energy payback time of the proposed distillation unit. Distillate production cost was increased by 16.0% for every 5 wt% increase in salt concentration. Amount invested in the unit can be regained with in 3.56 yr irrespective of interest rate for distilled water selling price of 0.06 USD/L (Rs. 3.91/L).